2018
DOI: 10.1038/s41699-018-0055-5
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-plane interface dipoles and anti-hysteresis in graphene-strontium titanate hybrid transistor

Abstract: The out-of-plane electric polarization at the surface of SrTiO 3 (STO), an archetypal perovskite oxide, may stabilize new electronic states and/or host novel device functionality. This is particularly significant in proximity to atomically thin membranes, such as graphene, although a quantitative understanding of the polarization across graphene-STO interface remains experimentally elusive. Here, we report direct observation and measurement of a large intrinsic out-of-plane polarization at the interface of sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 71 publications
(86 reference statements)
0
18
0
Order By: Relevance
“…19 In the rst case, this transition was explained by electrolyte insertion between graphene and the ferroelectric "compensating for anti-ferroelectric effects", while in the second it was "attributed to the dynamic response of interface screening charges that are activated by the combined effects of electric eld and temperature". It was then recognized that working in cleaner conditions is needed and a few years ago experiments were reported in vacuum in the range of 10 À3 to 10 À4 Pa. [20][21][22] Other precautions in terms of cleanness were undertaken, including thermal treatment. 1,23,24 However, the results were not concluding in all cases and it was acknowledged that even working in the above vacuum conditions, the inuence of chemisorbed OH À and H + cannot be ruled out.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 In the rst case, this transition was explained by electrolyte insertion between graphene and the ferroelectric "compensating for anti-ferroelectric effects", while in the second it was "attributed to the dynamic response of interface screening charges that are activated by the combined effects of electric eld and temperature". It was then recognized that working in cleaner conditions is needed and a few years ago experiments were reported in vacuum in the range of 10 À3 to 10 À4 Pa. [20][21][22] Other precautions in terms of cleanness were undertaken, including thermal treatment. 1,23,24 However, the results were not concluding in all cases and it was acknowledged that even working in the above vacuum conditions, the inuence of chemisorbed OH À and H + cannot be ruled out.…”
Section: Introductionmentioning
confidence: 99%
“…1,23,24 However, the results were not concluding in all cases and it was acknowledged that even working in the above vacuum conditions, the inuence of chemisorbed OH À and H + cannot be ruled out. 22 The charge carrier density in 1 ML graphene is insufficient to screen a polarization exceeding a few tenths of C m À2 , 2,14 see also the evaluation a few paragraphs below. In addition to the above mentioned hypotheses, other extrinsic compensation mechanisms were proposed, such as charge transfer driven by electronegativity differences between outermost atoms from ferroelectrics and carbon, 25 direct interaction of graphene with defects, which modify carbon hybridization from sp 2 to sp 3 or charge injection into interfacial traps, 1 dynamic accumulation of oxygen vacancies near the interface, forming a layer with different dielectric constant, 26 charge trapping prevailing over ferroelectric effects, 6 "intrinsic bulk ferroelectric hysteresis in combination of an oxygen-decient surface layer", 20 O 2 /H 2 O redox couple intermediated by graphene charging.…”
Section: Introductionmentioning
confidence: 99%
“…Further, antihysteresis in graphene square resistance, when back gated through STO has been reported by several groups and is an active area of research. 17 , 19 , 21 …”
Section: Introductionmentioning
confidence: 99%
“…The surface of STO has a broken inversion symmetry and is found to harbor surface dipoles where the oxygen atoms are displaced outwards . The strength of these surface dipole moments is calculated to be P=13.89 normalμnormalCcnormalm2 which increases to P=34.90 normalμnormalCcnormalm2 with the graphene layer . This electric field, pointing outwards from the substrate plane, originates from the surface dipoles in STO.…”
mentioning
confidence: 96%
“…Further, distinct from most other substrates on which charge and spin transport in graphene has been studied, the broken inversion symmetry at the surface of STO leads to Rashba spin orbit fields that can be tuned by an electric field . Recently it was demonstrated that electric dipoles, formed at the surface of STO, results in a large out of plane electric polarization that influences the charge transport in graphene . STO undergoes a ferroelastic transition changing from cubic ( a = 3.905 Å) to tetragonal symmetry (c/a=1.0056) at T = 105 K .…”
mentioning
confidence: 99%